2004
DOI: 10.1007/s10865-004-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choir Singing or Listening on Secretory Immunoglobulin A, Cortisol, and Emotional State

Abstract: The present study investigates the effects of choir music on secretory immunoglobulin A (S-IgA), cortisol, and emotional states in members of a mixed amateur choir. Subjects participated in two conditions during two rehearsals 1 week apart, namely singing versus listening to choral music. Saliva samples and subjective measures of affect were taken both before each session and 60 min later. Repeated measure analyses of variance were conducted for positive and negative affect scores, S-IgA, and cortisol. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
274
2
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(314 citation statements)
references
References 35 publications
21
274
2
17
Order By: Relevance
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 82%
See 1 more Smart Citation
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 82%
“…Small-scale choral studies with PD have shown improvements in QOL [40], speech intelligibility [41], breath control, and prosody [42]. Large-scale studies of choir participation with healthy older adults indicate improved QOL [43,44], social engagement [45,46], mood [47], immune functioning [48], and overall health [49].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…These authors found that music had a relaxing effect on participants and they attributed this finding to the release of the neurohormone melatonin. Other researchers found that levels of stress hormones, such as cortisol, were reduced in response to music and this factor led to a reduction of anxiety and improved immune system functioning (Avers et al, 2007;Kreutz et al, 2004). Most people enjoy listening to music and are aware of music's mood enhancing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative comparison has demonstrated that active group singing yields a greater increase in positive affect and decrease in negative affect compared both to passive listening to music (Kreutz et al, 2003; though see Unwin, Kenny, & Davis, 2002, where although there were no significant differences between singers and listeners, singers did show more robust changes) and discussing positive personal experiences (Kreutz, 2014). The elevated positive affect and hedonic feelings associated with group singing may lead to perception of greater well-being, which may also be tied into better mental health.…”
mentioning
confidence: 99%